Considerations for equitable distribution of digital healthcare for people who use drugs - Papalamprakopoulou, Zoi; Roussos, Sotirios; Ntagianta, Elisavet; Triantafyllou, Vasiliki; George Kalamitsis; Dharia, Arpan; Sypsa, Vana; Hatzakis, Angelos; Talal, Andrew H. (BMC Health Services Research, 2025)
Telehealth holds the potential to expand healthcare access for people who use drugs (PWUD). However, limited data exist on their digital infrastructure access, a prerequisite for telehealth participation. We studied digital healthcare accessibility among PWUD.